2022
DOI: 10.1021/acs.oprd.2c00107
|View full text |Cite
|
Sign up to set email alerts
|

Direct Synthesis of Methylchlorosilanes: Catalysts, Mechanisms, Reaction Conditions, and Reactor Designs

Abstract: Silicone polymers are produced commercially mainly from methylchlorosilanes prepared by direct synthesis. The yield and selectivity of this synthetic process depend not only on chemical reactions but also on transfer phenomena, leading to conflicting results and controversial interpretations within this research field. This review highlights recent advances in synthesis mechanisms, including catalysts and promoters, especially the effect of process parameters and reactor form on the reactivity and selectivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 82 publications
0
7
0
Order By: Relevance
“…The industrial process productivity is related to the reactivity (how much Si is converted) and selectivity (desired products vs byproducts) resulting from the adjustment of the reactor parameters, Si powder characteristics (chemical composition, microstructure, size distribution, etc. ), and additives (catalyst and promoters) . The direct synthesis is assumed to start with the adsorption of CH 3 Cl on the particle surface, and its subsequent decomposition into adsorbed CH 3 and Cl .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The industrial process productivity is related to the reactivity (how much Si is converted) and selectivity (desired products vs byproducts) resulting from the adjustment of the reactor parameters, Si powder characteristics (chemical composition, microstructure, size distribution, etc. ), and additives (catalyst and promoters) . The direct synthesis is assumed to start with the adsorption of CH 3 Cl on the particle surface, and its subsequent decomposition into adsorbed CH 3 and Cl .…”
Section: Introductionmentioning
confidence: 99%
“…), and additives (catalyst and promoters). 2 The direct synthesis is assumed to start with the adsorption of CH 3 Cl on the particle surface, and its subsequent decomposition into adsorbed CH 3 and Cl. 3 Adsorbed CH 3 can further decompose to CH 2 , CH, and C, producing an adsorbed H on the surface for each step.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Based on the EDS results, it was found that the first type of powder has bright white ferrosilicon particles attached to the surface, as shown in Figure 2b. The other type of powder particles have a mixture of Si and SiO 2 on the surface, with pits of different sizes as shown in Figure 2c, and there are pits of different sizes, which are caused by the erosion by copper during the preparation of organosilicon monomers using the Rochow-Müller process [15].…”
Section: Experimental Methodsmentioning
confidence: 99%
“…The presence of a solid reactant limits the precision of the reaction experiments and the possibility for extracting systematic data since there is no real steady-state, and it is difficult to ensure the absence of concentration and temperature gradients. The recent review by Zhang et al discusses how different catalysts and promoters in addition to the reactor design and process parameters influence the reaction rate and product distribution of the MCS process. The fluidized bed laboratory arrangement adopted in the present work has been developed by Elkem over decades and has demonstrated good reproducibility and capability with respect to extracting valuable insights. In the present work, the protocol was extended to disentangle the effects of the reaction time and Cu/Si ratio in conjunction with the effect of the Zn promoter.…”
Section: Methodsmentioning
confidence: 99%
“…The reaction between chloromethane (CH 3 Cl, also called methyl chloride) and silicon (Si) to synthesize methylchlorosilanes (MCS), also known as the Müller-Rochow Synthesis or the Direct Process, is currently the most convenient and economical way to produce MCS industrially. Almost 90% of the starting materials for current silicone manufacturing are obtained with MCS monomers. On an industrial scale, ground metallurgical grade silicon is mixed with a copper-based catalyst and minor amounts of various other promoter elements in a fluidized bed reactor under gaseous CH 3 Cl, at temperature and pressure ranging between 280–350 °C and 1–10 bar. , This quite unique gas (CH 3 Cl)–solid (Si)–solid (Cu-based catalyst) heterogeneous reaction exhibits a complicated dependency on reaction temperature, (partial) pressure(s), reactor type, residence time distribution, and phase/component interactions. , The latter incorporates nature, purity, size distribution, morphology, and proportion of silicon to copper catalyst precursor and promoters . Moreover, a range of methylchlorosilanes, (CH 3 ) x SiCl 4– x , is formed although the dominant and main product of interest is dimethyldichlorosilane, (CH 3 ) 2 SiCl 2 , also referred to as “M2” .…”
Section: Introductionmentioning
confidence: 99%